S131 Iron chelation reduces lung cancer proliferation in vitro. (14th November 2013) - Kay, J; McNab, G; Newby, P; Bedford, M; Turner, A
Abstract : Introduction: There is growing evidence that iron plays an important role within the lung cancer, the leading cause of cancer-related mortality worldwide. As a result of this, iron homeostasis has potential as a new avenue for targeting and treatment of lung cancer. In this study, the effect of iron loading on cellular proliferation and iron homeostasis gene expression was investigated. In addition, the effect of the chelator deferasirox on cellular iron levels and proliferation rates was studied. Methods: Cellular proliferation was assessed by the BrdU assay and cellular iron levels were assessed using the ferrozine assay. Manipulation of IREB2 gene expression was achieved using short interfering RNA (siRNA) and subsequent expression of this and other iron homeostasis genes was assessed using real time PCR. All experiments were carried out on both the A549 adenocarcinoma and QG56 squamous cell carcinoma cell lines in triplicate. Primary bronchial epithelia cells (PBEC) were used as reference of normal behaviour. Results: A dose of 150uM of iron was seen to cause a significant increase in proliferation in both the A549 (50% increase) and QG56 (40% increase) cell lines (P = 0.002 and 0.03 respectively) whilst no change was seen in the PBECs. A corresponding increase in cellular iron was also seen.When the cancer cell lines were treated with deferasirox, cellular iron loading decreased by roughly 25% in each cell line (P = 0.001 and 0.01 respectively) and cellular proliferation decreased below levels seen in unstimulated cells. Deferasirox was also seen to effect unstimulated cancer cells, reducing their proliferation by 50% (P = 0.02 and 0.03 respectively). Conclusion: Iron exposure was shown to have a significant effect on cellular proliferation within lung cancer cell lines, although the underlying mechanism is not yet fully understood. This iron mediated cellular proliferation could be reversed using the chelator deferasirox. Down-regulated expression of IREB2 may cause the cancer cell lines to exhibit similar behaviour to the PBECs when stimulated with iron. These finding show that iron may provide a potential new target and deferasirox a potential new therapeutic agent for lung cancer.